Aplikasi System Informasi Geografi (SIG) Dalam Pembuatan Peta Rawan Longsor Pada Desa Kaseralau Kecamatan Batulappa Kabupaten Pinrang: - - Angraini. A, Nurvadillah; Muh. Said (SAINFIS: Jurnal Sains Fisika, 2025)
Indonesia is one of the countries in Southeast Asia located between two continental plates and two oceanic plates, causing the Indonesian region to have diverse morphological forms, one of which is the plateau or hills that have sloping and steep land fields. Indonesia is also a country crossed by the equator, so that Indonesia has two seasons, namely the dry season and the rainy season. This research aims to apply geographic information system (GIS) in making landslide prone map in Kaseralau village, Batulappa sub-district, Pinrang district. This research was conducted in Kaseralau Village, Batulappa Sub-district, Pinrang Regency. The data processing method used is using Arcgis software for mapping. In the mapping, parameters such as rainfall, slope, geomorphology, soil type and geology are required. Based on the results obtained from the research data using GIS software, the level of landslide vulnerability in Kaseralau Village, Batulappa Sub-district, Pinrang Regency is obtained, namely for low vulnerability level with a distribution percentage of 6%, for medium vulnerability level with a distribution percentage of 10%, and for high vulnerability with a distribution percentage of 84%. This data is reinforced by GIS data in the form of slope, geomorphology, rainfall, soil type, and geological conditions as well as field survey results in the form of photos.